Anthropomorphic Metaphors of time in Modern Lithuanian Poetry - Juzelėnienė, Saulė; Seredžiūtė, Viktorija; Šarkauskienė, Skirmantė (Respectus Philologicus, 2012)
Time is one of the most important categories related to human existence. Like all abstracts, the conceptualization of time is based on certain experience structures stored in our minds. Time studies in the Lithuanian language are not new—it has been analyzed in poetry, riddles and folk songs. This article aims to analyze the anthropomorphic metaphors used in contemporary Lithuanian poetry. The study material consists of samples collected from modern poetry collections. The study shows that time in Lithuanian poetry is conceptualized as a human being, having both physical and spiritual attributes, gender, and socialization. Therefore, all the anthropomorphic metaphors can be divided into a few categories: 1. Time and the Human Body, 2. Time and Movement/Action, 3. Time and Physiology, 4. Time and Gender, 5. Time and Emotion, 6. Time and Perception, 7. Time and Power, and 8. Time and Social Relations. The study reveals that time in modern Lithuanian poetry tends to have rather negative connotations. The negative connotations are mostly related to the category of Time and Emotions, and to metaphors of the Time and Power group. Negative connotations are associated with the dark periods of time: autumn, night, evening. There are only a few positive connotations; they are related to the Time and Emotion, Time and Power and some Time and Body metaphor groups. In modern Lithuanian poetry, certain signs of opposition, reflecting ambivalence in the perception of time, are displayed: time as a powerful or powerless person, time as a creator or a destroyer, time as a man or a woman, time as a stupid or smart person, time as an enjoying or melancholic person, time as a beggar or a ruler.